Public support for inclusionary housing in urban China. Issue 4 (2nd October 2019) - Chen, Zhigang; Huang, Youqin; Huang, Xianjin
Abstract: In recent years, China has been experimenting with inclusionary housing to develop affordable housing and promote mixed living in cities. There is thus an urgent need to understand residents' preferences and public support for inclusionary housing, which is important not only for the design and implementation of inclusionary housing but also for political legitimacy and social stability. This study developed a conceptual framework to understand public support for inclusionary housing. Hypotheses derived from the self-interest, ideology and institutional setup theses were then developed. A two-level mixed effect logit model was also conducted using data from a 2013 survey in Jiangsu Province. Results indicated that most people preferred inclusionary housing to concentrated low-income housing; all three theses were supported to some degree. People of lower socioeconomic status, recipients of housing subsidies, and those living in cities with significant low-income housing coverage rates were more likely to support inclusionary housing. On the other hand, migrants were less likely to support this measure. The effectiveness of inclusionary housing was also discussed and policy recommendations were provided.